Detection of urinary cystatin-c in IUGR neonates by immunoblot SDS-PAGE - Chiara Grasselli (Elsevier, 2022)
Background: it is known that intrauterine growth retardation (IUGR) represents a risk factor for the deterioration of renal function as it can adversely impact on the number of nephrons developed in the kidney during nephrogenesis. An interesting molecule is the Cystatin-C (cyst-C): it is considered to have the potency to detect both glomerular and proximal renal injury. Recently, using a quantitative EIA cyst-C detection kit, we found increased levels of cyst-C in the urine of neonates with IUGR. Since cyst-C molecules can be present in both monomer and/or polymer forms, the purpose of this study is to investigate in which forms this molecule is present in the urine of IUGR neonates by Immunoblot SDS-PAGE in order to verify if the presence or absence of a particular type of cyst-C conformation can give more information about the renal functioning. Methods: urine samples were collected from 64 neonates with IUGR, and 86 healthy controls defined as appropriate for gestational age (AGA). Urinary cyst-C was investigated by the Immunoblot SDS-PAGE. Results: in all urine samples, SDS-PAGE analysis showed a reactivity of the IgG anti cyst-C with a complex of about 70 kDa. The monomer form at 13 KDa appeared in 78% of IUGR neonates and in 12% of AGA neonates. Conclusions: this study revealed the presence of monomer cyst-C in the urine of IUGR neonates, and suggests an insufficient and/or non-compensatory reabsorption by tubular cells. Monomeric cyst-C can be considered an early biochemical marker to identify and to select IUGR neonates who need to be monitored for risk of renal injury.